Analisis Puisi Karo “Sinabung Sayang” Karya Priska Natalia Milala dengan Menggunakan Pendekatan Mimetik - Selvy Afrina Br Sembiring; Reza Pahlevi Ginting (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This research aims to examine how mimetic phenomena convey meaning in the literary work of poetry "Sinabung Sayang" by Priska Natalia Milala. Apart from that, research is also focused on mimetics, namely imitation of natural phenomena that represent emotional feelings and atmosphere. The method used in this research is a qualitative method, because it analyzes mimetic concepts and describes the meaning intended by the author of the poem. The mimetic concept used in this research is a combination of Plato's and Aristotle's mimetic concepts. As is known, these two concepts have different meanings. As a result, a natural phenomenon was discovered: a volcano erupted. Apart from that, there are also imitation emotions: sadness, calm, and fear. This research is useful for understanding the message conveyed by the author to the readers of this poem.